Seismic Analysis of Multi Storey Buildings With and Without Shear-Walls - Dalai, Tejaswini; Parhi, Pravat Kumar (AMC Indian Journal of Civil Engineering, 2021)
A structure in its design life period is subjected to a number of earthquakes of various intensities from small to medium and large. The work of a structural engineer is to come up with a design that will be able to resist the impact of earthquake without collapse. Earthquake resisting members like shear-walls are ductile in nature and they exhibit enough resistance to face the seismic forces and reduce the amount of drifts and displacements. In this study, an under 50m category building (twelve storey, G+11, total height 36m) and a 50-100 m category building (twenty-eight storey, G+27, total height 84m) are considered with and without shear-wall configuration for seismic analysis. Both static and dynamic analysis are applied to the structures using ETABs software. Difference in results for drifts and displacements are studied in this investigation.